2017
DOI: 10.1002/bjs.10493
|View full text |Cite
|
Sign up to set email alerts
|

Non-technical skills of surgical trainees and experienced surgeons

Abstract: The drop in NOTSS score was unexpected and highlights that even experienced surgeons are not immune to deficiencies in non-technical skills. Consideration should be given to continuing professional development programmes focusing on non-technical skills, regardless of the level of professional experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…One study suggested that adequate patient safety education could equip qualifying healthcare professionals with the same safety skillset as their seniors 42. Another recent study evaluating the non-technical skills of surgeons at various levels of training concluded that these skills peak around fellowship and then decline with years postfellowship experience, highlighting the importance of interventions that facilitate continued professional development 43. Undergraduates have proven to be valuable team members in error prevention44 and are well placed to spread patient safety culture throughout training rotations; students have not developed their own routine practice and often engage with initiatives through social media and technological advancements 45…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that adequate patient safety education could equip qualifying healthcare professionals with the same safety skillset as their seniors 42. Another recent study evaluating the non-technical skills of surgeons at various levels of training concluded that these skills peak around fellowship and then decline with years postfellowship experience, highlighting the importance of interventions that facilitate continued professional development 43. Undergraduates have proven to be valuable team members in error prevention44 and are well placed to spread patient safety culture throughout training rotations; students have not developed their own routine practice and often engage with initiatives through social media and technological advancements 45…”
Section: Discussionmentioning
confidence: 99%
“…Studies which do follow up participants show NTS retention for at least 2 months in current training programmes, in which some claiming trainees are still benefitting at 6 months, but others note that there is no significant difference between the NoTSS scores of surgeons who have previously undertaken NTS training versus those who have not. These studies often employ a second simulation session to record improvement and do not look at real performance in the OR [23,26,35]. The longer-term effects of any courses are yet to be shown, but repeat training is necessary to maintain skills after they are learnt initially and make sure they translate to practice [35].…”
Section: Retention Of Knowledgementioning
confidence: 99%
“…These studies often employ a second simulation session to record improvement and do not look at real performance in the OR [23,26,35]. The longer-term effects of any courses are yet to be shown, but repeat training is necessary to maintain skills after they are learnt initially and make sure they translate to practice [35]. This poses two unanswered questions: how frequent should NTS training be and how should 'refresher' courses be structured [23,26]?…”
Section: Retention Of Knowledgementioning
confidence: 99%
See 2 more Smart Citations